Hospitalization Rate and Population-based Incidence of Hospitalization for Community-acquired Pneumonia Among Children in Suzhou, China. Issue 12 (December 2018) - Shan, Wei; Shi, Ting; Zhang, Xiyan; Xue, Jian; Wang, Yin; Yu, Jia; Huang, Yukai; Lin, Sheng; Zhao, Genming; Tian, Jianmei; Zhang, Tao
Abstract : Background: Data on hospitalization burden of community-acquired pneumonia (CAP) in children are very limited in China. This study aimed to estimate the hospitalization rate (HR) and population-based incidence of hospitalization of CAP for children <15 years of age in Suzhou, China. Methods: This was a retrospective study of children hospitalized in Soochow University Affiliated Children's Hospital from January 2010 to December 2014. Children who were residents of downtown Suzhou, 29 days to <15 years of age, with discharge diagnosis codes (International Classification of Diseases, 10th revision) including J09–J18 and J20–J22 were included. All-cause clinical community-acquired pneumonia (CCAP) and radiographically confirmed pneumonia (RCAP) were identified based on individual medical chart review. The HR and population-based cumulative incidence of hospitalization (HI) were calculated. Results: Among 184, 734 children <15 years of age admitted to Soochow University Affiliated Children's Hospital during the study period, 31, 302 children were identified as having CCAP and 24, 218 (77.4%) children confirmed as having RCAP. CCAP hospitalization occurred year round and peaked during winter and early spring. The overall HRs for CCAP and RCAP were 189.0 [95% confidence interval (CI): 187.1–190.9] and 146.2 (95% CI: 144–148) per 1000 hospitalizations, respectively, and the HIs per 100, 000 children annually were CCAP, 3235.8 (95% CI: 3207.3–3264.2) and RCAP, 2503.5 (95% CI: 2478.3–2528.6). For children <5 years of age, the HR for CCAP was 248.4 (95% CI: 245.9–250.9) and RCAP was 194.0 (95% CI: 191.4–196.3) per 1000 hospitalizations; the HI for CCAP was 6956.2 (95% CI: 6892.8–7019.6) and 5431.9 (95% CI: 5375.4–5488.4) per 100, 000 children for RCAP. The highest HR and HI were observed in children 29 days to <6 months of age: HR for CCAP was 407.4 (95% CI: 400.9–413.9) per 1000 hospitalizations and HI for CCAP was 11, 203.7 (95% CI: 11, 026.8–11, 380.6) per 100, 000 children annually. Conclusions: There is a considerable burden of CAP among children <15 years of age in Suzhou, particularly among children 29 days to <6 months of age and during winter and early spring. These data provide valuable information to monitor CAP trends over time in children of Suzhou, China.